Faktor-Faktor Pendukung Kerjasama Guru Bimbingan dan Konseling dengan Guru Mata Pelajaran dalam Pelayanan Bimbingan dan Konseling di SMK Negeri 3 Metro Tahun Pelajaran 2018/2019 - Veronika Mursiti (Citra Dharma Cindekia, 2022)
The purpose of this study was to determine the factors supporting the cooperation of guidance and counseling teachers with subjects in guidance and counseling services. The research design used is a qualitative approach. The subject of the research is the teacher of guidance and counseling, subjects. Collecting data using interviews and observation. Data analysis using data reduction, data presentation and drawing conclusions testing the validity of the data is done by increasing the persistence of observations. The research design used is a qualitative approach. The research subjects are Guidance and Counseling teachers, subjects. Collecting data using interviews and observation. Data analysis using data reduction, data presentation and drawing conclusions testing the validity of the data is done by increasing the persistence of observations. The conclusion of this study is that there are several factors supporting the cooperation of Guidance and Counseling teachers in collaboration with subjects in Guidance and Counseling services, namely Guidance and Counseling Teachers and subject teachers who have awareness about their own abilities and others, Guidance and Counseling teachers and subject teachers. realize that in dealing with student problems, the background of the problem must be known so that it can be resolved immediately. Guidance and Counseling teachers and subject teachers communicate intensely about student development, Guidance and Counseling teachers and subject teachers need understanding from each party, Guidance and Counseling teachers provide guidance to subject teachers in collaboration, Guidance and counseling teachers and eye teachers learning to be open and trust each party.